Handgrip Strength and Its Relationship with White Blood Cell Count in U.S. Adolescents - Garcia-Hermoso, A (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
Background: The role of muscular fitness (as a protecting factor for an optimal immune system) and WBC count remains unclear. To the best of our knowledge, this is the first study to investigate the relationship between the total count of WBC and groups based on handgrip strength and body composition. The aim of this study was to elucidate the relationship between handgrip strength and WBC count in a nationally representative sample of adolescents from the U.S. Methods: We used data from the NHANES cross-sectional study (waves 2011 to 2014). The final analysis included 917 adolescents from 12–17 years old (51.0% boys). Normalized handgrip strength (kg) (NHS) was relativized by body composition parameters (body weight [NHSw], total body fat [NHSf], and trunk fat [NHSt]) assessed with dual energy X-ray absorptiometry. Results: An inverse association was found between total WBC count and all assessments of low NHS in both sexes (p < 0.05). Both boys and girls with low NHS had higher WBC counts in all estimations of NHS than those with high NHS (p < 0.05 for all). All estimations of low NHS showed significant differences with those with intermediate NHS (only in girls) (p < 0.05 for all). Girls with intermediate NHSt exhibited higher WBC count than those with high NHSt (p = 0.004). Conclusions: Our findings suggest that greater levels of NHS are linked to lower total WBC counts. From a public health perspective, our findings are clinically significant and emphasize the relevance of improving muscular fitness during adolescence since it may contribute to boosting the immune system among adolescents. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.